2020
DOI: 10.3390/min10080691
|View full text |Cite
|
Sign up to set email alerts
|

Lower Cretaceous Rodby and Palaeocene Lista Shales: Characterisation and Comparison of Top-Seal Mudstones at Two Planned CCS Sites, Offshore UK

Abstract: Petroleum-rich basins at a mature stage of exploration and production offer many opportunities for large-scale Carbon Capture and Storage (CCS) since oil and gas were demonstrably contained by low-permeability top-sealing rocks, such as shales. For CCS to work, there must be effectively no leakage from the injection site, so the nature of the top-seal is an important aspect for consideration when appraising prospective CCS opportunities. The Lower Cretaceous Rodby Shale and the Palaeocene Lista Shale have acte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…9 Studies have reported shales with column heights greater than 300 m as having good CO 2 seal capacity. 13,14 In this study, the CO 2 column height (Figure 10) reveals the samples as being characterized by good seal capacity due to their ability to prevent the flow in a CO 2 saturated column above 290 m on average. Furthermore, apart from the ankerite deficient Ilaro-1, CO 2 heights (Figure 10) obtained from mesoporedominated samples greater than 300 m. Recently, the carbonate-rich Rodby shale with an average column 396 m was deduced as being characterized by a decreasing tendency to fracture during CO 2 injection due to carbonate dissolution.…”
Section: Discussionmentioning
confidence: 65%
See 2 more Smart Citations
“…9 Studies have reported shales with column heights greater than 300 m as having good CO 2 seal capacity. 13,14 In this study, the CO 2 column height (Figure 10) reveals the samples as being characterized by good seal capacity due to their ability to prevent the flow in a CO 2 saturated column above 290 m on average. Furthermore, apart from the ankerite deficient Ilaro-1, CO 2 heights (Figure 10) obtained from mesoporedominated samples greater than 300 m. Recently, the carbonate-rich Rodby shale with an average column 396 m was deduced as being characterized by a decreasing tendency to fracture during CO 2 injection due to carbonate dissolution.…”
Section: Discussionmentioning
confidence: 65%
“…Furthermore, apart from the ankerite deficient Ilaro-1, CO 2 heights (Figure 10) obtained from mesoporedominated samples greater than 300 m. Recently, the carbonate-rich Rodby shale with an average column 396 m was deduced as being characterized by a decreasing tendency to fracture during CO 2 injection due to carbonate dissolution. 14 is because 2 trapping via interactions with carbonate or feldspar is due to the dissolution of Ca or Mg that results in the of secondary carbonates, which trap the injected CO 2 . 4 Carbonates have a higher affinity to this compared to feldspar, with quartz having the lowest.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This Special Issue on "Characteristics of Mudrocks: Textures and Mineralogy" contains seven papers, representing the works of 32 researchers in aspects related to the field of mudrock research. Areas covered include petroleum exploration [1], carbon capture and storage [2], diagenesis [3], environmental interpretation [4,5] and new techniques [6]. These papers should be of interest to all those interested in the field of mudrocks.…”
mentioning
confidence: 99%
“…Worden, Allen, Faulkner, Utley, Bond, Alcalde, Heinemann, Haszeldine, Mackay and Ghanbari describe and discuss the characteristics of two important North Sea mudstone units that will act as top seals for the underlying storage of CO 2 in planned carbon capture and storage (CCS) schemes (Acorn and East Mey CCS) [2]. Wireline logs, geomechanical tests, special core analysis and mineralogical and petrographic techniques are used to demonstrate the potential of wireline logs as a predictor of Young's modulus and thus the susceptibility of top seals to brittle fracture and the development of fracture leakage pathways.…”
mentioning
confidence: 99%